A study on glycerolysis of oil palm empty fruit bunch fiber - Siti Munirah Ibrahim,; Khairiah Haji Badri,; Osman Hassan, (Universiti Kebangsaan Malaysia, 2012)
Lignocellulose from oil palm empty fruit bunch fiber (EFB) has been identified as another source for conversion into renewable energy or value added products. Cellulose, hemicellulose and lignin were extracted from EFB via a new treatment method using aqueous glycerol as a potential delignification agent. The aim of this study was to investigate the effect of treatment time and EFB to solvent ratio on the analytical compositions of EFB with or without further treatment with aqueous glycerol. The cooking time was varied at 3, 5 and 7 h with temperature fixed at 85°C. Three types of EFB were used; untreated fiber (UT-EFB), pretreated fiber with 5% (w/v) sodium hydroxide solution (N-EFB) and pretreated fiber with 5% (w/v) acetic acid solution (A-EFB). The analyses carried out were determination of extractives content, Klason Lignin, α-cellulose, hemicelluloses, holocellulose and ash content based on dry weight of the EFB. An increase in the glycerolysis time resulted in reduced content of Klason lignin and extractives but high percentages of holocellulose and α-cellulose for all EFB samples. Treatment of EFB with alkaline solution prior to glycerolysis resulted in reduction in cellulose content compared with holocellulose.